2013
DOI: 10.15275/rusomj.2013.0107
|View full text |Cite
|
Sign up to set email alerts
|

Pathomorphological distinction between Er:YAG and diode lasers on the excisional biopsy of the oral mucosa

Abstract: Background -In oral pathology, laser devices can provide important advantages, especially in the treatment of certain lesions. However, there is controversy about the use of some wavelengths in the analysis of suspected dysplastic or neoplastic lesions, raising doubt about the laser's suitability for use in biopsy procedures. The present pilot study evaluates the pathomorphological characteristics and suitability of Er:YAG and diode lasers for performing excisional biopsies in the oral mucosa with special emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Water is the dominant target chromophore for Er:YAG laser energy which currently has the highest absorption peak in water among any commercially available, FDA-approved dental lasers. These unique characteristics of the Er:YAG laser allow performing of very narrow layers of thermal mechanical tissue ablation with minimal collateral thermal consequences [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water is the dominant target chromophore for Er:YAG laser energy which currently has the highest absorption peak in water among any commercially available, FDA-approved dental lasers. These unique characteristics of the Er:YAG laser allow performing of very narrow layers of thermal mechanical tissue ablation with minimal collateral thermal consequences [8].…”
Section: Discussionmentioning
confidence: 99%
“…This can be accomplished because of the unique characteristics and photobiology of the Er:YAG laser tissue interaction. In contrast to other laser systems the Er:YAG does not have haemostatic properties, but the healing process after Er:YAG laser surgery is faster, without thermal damages and necrosis [8]. With the addition of the Er:YAG laser, the general dentist is presented with a less stressful and more beneficial treatment protocol for soft-tissue excisional procedures than previously available with the older continuous wave diode or pulsed CO 2 lasers alone [9].…”
Section: Oral Soft Tissue Laser Proceduresmentioning
confidence: 99%
“…The main plus compared to the other instruments is the water cooling, which makes the manipulations more gentle, the reactions (pain, edema and erythema)vague and the healing processfaster (3,5,7,8,9,10,12). The diode laser has a lot of advantages as well, although its results compared to the others are poor (3,4,6,7,12). The coagulation and hemostasis in-depth are well defined, which from the clinical point of view equals lack of bleeding.…”
Section: Width Of the Coagulation Layermentioning
confidence: 99%
“…Er: YAG lasers are not well absorbed in hemoglobin as the soft tissue diode lasers are, so hemostasis can be an issue with these wavelengths. Some studies [18][19][20][21][22][23] compared the efficacy of diode and Er: YAG lasers in soft tissue oral surgery. Some studies showed that the Er:YAG laser induced deeper gingival tissue injury than diode laser, as judged by bleeding at surgery, delayed healing and deformed specimen for histopathological analysis [23].…”
Section: Mean (μM) ± Sdmentioning
confidence: 99%
“…Some studies [18][19][20][21][22][23] compared the efficacy of diode and Er: YAG lasers in soft tissue oral surgery. Some studies showed that the Er:YAG laser induced deeper gingival tissue injury than diode laser, as judged by bleeding at surgery, delayed healing and deformed specimen for histopathological analysis [23]. In some studies the use of diode laser showed additional advantages over Er: YAG in terms of less postoperative discomfort and pain, but some studies show no difference between these two lasers [3].…”
Section: Mean (μM) ± Sdmentioning
confidence: 99%